A DEA model for resource allocation - Hadi-Vencheh, Abdollah; Foroughi, Ali Asghar; Soleimani-damaneh, Majid (Economic modelling, 2008)
This paper concerns inverse DEA. The aim is to estimate input/output levels of a given Decision Making Unit (DMU) when some or all of its input/output levels are changed, under preserving the efficiency index. We show that in the case of estimating increased required input vector when the output vector is increased, the current method which uses weakly efficient solution of the relevant multiple objective optimization problem may fail. We propose some sufficient conditions for input estimation.